TINJAUAN YURIDIS TERHADAP KLAUSULA âPENGEMBALIAN BIAYA OPERASIâ (COST OPERATING RECOVERY ) PADA STANDARD KONTRAK PERJANJIAN BAGI HASIL (PRODUCTION SHARING CONTRACT STANDARD) MINYAK DAN GAS BUMI PERTAMINA DALAM HUBUNGANNYA DENGAN ASAS KESEIMBANGAN DALAM HUKUM PERJANJIAN - , Slamet Djatmiko, SH ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The purpose of this paper is to determine the substance of the clause "cost recovery" operation (the recovery of operating costs) in the standard contractual agreement to result in juridical terms in relation to the principles of balance and knowing the possibility of making a contract agreement deed division of roles Production Sharing Contract between the oil and gas Pertamina and foreign oil companies. Research Testing clause Operating Cost Recovery in the Standard Production Sharing Contract Oil and Gas, Pertamina, together with the Principle of Balance in the Law of Treaties is normative studies, The sampling technique is by way of purposive sampling, which has been determined that the source has a relevance to the topic of research, such as Prof. Dr Iman Sugema, PhD, Director of the International Center for Finance and Applied Economics (InterCAFE) and simultaneously head of the Graduate Program, Bogor Agricultural University, Prof. Widjajono Partowidagdo, MSc, MA, Ph.D. as Professor of Economics and Management of Oil and Gas Field in the Faculty of Mining and Petroleum Engineering, National Assembly Member of the Commission of Professors Problems Institute of Technology Bandung (ITB), and Mr M. Agus Imaduddin, Head Division of Law Oil and Gas (BP Migas), Pertamina, Jakarta. The results showed that the substance of the principle of balance in the clause the recovery of operating costs in the standard contractual agreement to the terms of juridical not in accordance with the principle of balance. On the substance of the implementation of recovery clausula cost recovery in relation to the principle of balance, the results of the study, with findings from the government that show state interference 18,070,000,000,000 rupiah (Prof. Dr. Iman Sugema, PhD (December 11, 2007)). It can be concluded that the implementation of cost recovery is not in accordance with the principle of balance. Possible role of notaries in the manufacture of the Production Sharing Contract (PSC) is probable. Notary is authorized to create an authentic deed. Will of each party in the collective agreement that is poured into authentic documents provide evidence that's perfect for parties. On the Production Sharing Contract (PSC), which contain high risk require evidence in writing, so the agreement of the parties to the Agreement or Production Sharing Contract Production Sharing Contract (PSC), which contains a high risk should be poured into a notarial deed .